Gene effects, heterosis and inbreeding depression in Pigeonpea, Cajanus cajan L. - C.V.Sameer Kumar, Ch.Sreelakshmi and D.Shivani (Electronic Journal of Plant Breeding, 2012)
The P1, P2, F1, F2, B1 and B2 of four pigeonpea, Cajanus cajan L. crosses were studied for eight metric traits. Individualscaling tests and joint scaling test indicated that an additive-dominance model was adequate in viz., PRG 100 x ICPL 87119,LRG 300 x ICP 8863 for number of primary branches per plant and LRG 300 x ICP 87119 for number of primary branches perplant and number of pods per plant. The results of the rest of the cases suggested the presence of additive, dominance andepistatic gene effects especially for the traits viz., seed yield and test weight.. Duplicate type of epistasis was prevalent in most ofthe cases. A substantial amount of heterobeltiosis over better parent (HBP) was revealed in all the four crosses for seed yield perplant and for most of its attributes. Inbreeding depression was also observed significant for days to 50% flowering, days tomaturity and number of clusters per plant in the cross PRG 100 x ICPL 87119 indicating the presence of dominance gene action.Suitable breeding strategies were suggested for the improvement of seed yield in pigeonpea.